A multi-domain BEM based on dual interpolation boundary face method for 3D elasticity problem. (October 2022) - Chai, Pengfei; Zhang, Jianming; Xiao, Rongxiong; He, Rui; Lin, WeiCheng
Highlights: DiBFM-HMLS is used in 3D potential multi-domain problem. Hermite-type moving-least-squares method is used to supplement additional equations for interfacial virtual points. A node-to-element interfacial condition is built to satisfy a flexible mesh division (e.g. self-adaption problem). The multi-domain DiBFM-HMLS is more efficient than the single-domain DiBFM-HMLS. Abstract: The dual interpolation boundary face method with Hermite-type moving-least-squares approximation (DiBFM-HMLS), presented recently, has certain advantages in simulating the discontinuous fields. Based on the DiBFM-HMLS and the matrix condensation technique, we proposed a multi-domain method for 3D elasticity problems in this paper. This method ensures an accurate interpolation for the multi-domain models with short edges or small chamfers. In the multi-domain DiBFM-HMLS, the virtual points in each subdomain, not as collocation points in the boundary integral equation (BIE), are eliminated by the HMLS approximation separately. Then, only the interfacial source points are reserved by the matrix condensation technique. The node-to-node interfacial condition in previous research is unemployed; instead of the former, a node-to-element format is constructed based on the moving-least-squares approximation (MLS). This mapping scheme possesses the potential for free mesh in the interface. Several numerical examples are used to reflect these advantages mentioned above.